Pengaruh Pemberian Reward terhadap Motivasi Belajar Peserta Didik dalam Pembelajaran PAI Kelas 4 SDN 01 Ulak Karang Selatan - Haida, Aufa Melti; Wirdati, Wirdati (ALSYS, 2024)
This study aims to find out how giving rewards affects the learning motivation of class 4th students in Islamic Education at SDN 01 Ulak Karang Selatan. The research was conducted from April to May 2024 at SDN 01 Ulak Karang Selatan. A Quantitative method with a Pre-Experimental Design was used. Data were collected using questionnaires with a Likert scale. The Likert scale had four options: A, B, C, and D. There were two types of questionnaires: one for rewards and one for motivation. Data analysis included Descriptive Statistical Test, Classical Assumption Test, and Hypothesis Testing using SPSS Software Version 26. The T-test results showed a significance value of 0.000, which is less than 0.05. This means the independent variable (reward) significantly affects the dependent variable (motivation). The adjusted R-Squared value showed that the control class had a determination coefficient of 0.604 or 60%, and the experimental class had a determination coefficient of 0.881 or 88%. Comparing these values, it was concluded that the treatment in the experimental class had a positive effect, with a 28% difference between the control and experimental classes. Therefore, giving rewards in education proves to impact students' learning motivation.